Association of dominated tree species in lowland tropical forest of Tangkoko Nature Reserve, Bitung, North Sulawesi - AGUNG KURNIAWAN; NI KADEK EROSI UNDAHARTA; I MADE RAHARJA PENDIT (Biodiversitas Journal of Biological Diversity, 2008)
The study aimed to gain information about tree species domination and association was conducted in lowland tropical forest of Tangkoko Nature Reserve. The tree with â‰¥10 cm dbh censused with quarter method. The result showed that Palaquium sp. having the highest domination species with Index Importance Value 21.05, as well as Cananga odorata Hook.f. & Thoms. and Dracontomelon dao (Blanco) Merril & Rolfe. There was one couple species that had positive association among seven main species composition in area study, that was C. odorata with kayu kapur. Generally, the other couples species had negative association, so there was no tolerance to exist in the same area and no mutualism interrelationship especially in habitat grouping.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Palaquium sp., domination, species association, Tangkoko Nature Reserve